Strontium-90 in human bones and teeth in Greece: Measurements and predictions using an age-dependent model - Stamoulis, K. C.; Assimakopoulos, P. A.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2020)
Strontium-90 concentration in human bones and teeth, collected in Greece during the period 1992-1996, was measured. One hundred and five bone samples, mainly cancelous (spongy) bone, and 108 samples, involving a total of 896 individual teeth, were processed. Samples were classified according to age and sex of the donors. Radiostrontium concentration in bone samples showed small variations with regard to age or sex, yielding an average value of 30 mBq concentration measurements in teeth evinced a pronounced structure, which clearly reflects contamination from the 1960s atmospheric nuclear weapons tests and the more recent Chernobyl accident. This difference is attributed to the different bone texture of skeletal bones and teeth, the later consisting mainly of compact bone. An age-dependent model for radiostrontium concentration in human bones and teeth was developed, which was able to successfully reproduce the experimental data. Through a fitting process, the model also yielded calcium turnover rates for compact bone as a function of age, as well as an estimate of radiostrontium con- tamination of foodstaffs in Greece for the past four decades.